Voltar para frente: construções na clínica psicanalítica da psicose - Clausse, Evelyse Stefoni de Freitas (2009)
The purpose of this work is to define a way of intervention in the psychoanalytic treatment of psychosis. Rooted in Fundamental Psychopathology, it is a case study, based on clinical method, conveyed by the search of a patient for its origins. To tackle the question of origins, we start with the myth of Oedipus, the gate to the introduction of the patient into culture, out of the construction of the myth of the origin of civilization, as well as out of the subjective experience, whose course through the Oedipus complex, from the symbolization of the primordial law, will produce different modes of subjectification. Our route begins with the investigation of the first issue that brought us to the clinic: the not knowing . From a patient who comes to the consulting room overwhelmed by learning diffculties at school and, above all, by his not knowing about his own origin, we are invited to investigate the hardship of knowledge and cognition and its implications in the psychical constitution. From these notions, we will address the different aspects of intellectual inhibition in childhood clinic where do appear, separated by stringent limits: the symptomatic position in which inhibition would serve as a defense against the confrontation of the neurotic conflict or the intellectual insufficiency as a visible phenomenon in childhood, a mask for psychosis. Along the case, we introduce the psychical constitution through psychosis, whose understanding is based in the rupture of the primordial symbolization. Back to the question of origins, we discuss the notions of fantasy, delirium and family romance. Finally, we address the task of the psychoanalyst in the treatment of psychosis